"Very Good" Ratings in a Survey of Maternity Care: Kindness and Understanding Matter to Australian Women. Issue 1 (15th November 2016) - Todd, Angela L.; Ampt, Amanda J.; Roberts, Christine L.
Abstract: Background: Surveys have shown that women are highly satisfied with their maternity care. Their satisfaction has been associated with various demographic, personal, and care factors. Isolating the factors that most matter to women about their care can guide quality improvement efforts. This study aimed to identify the most significant factors associated with high ratings of care by women in the three maternity periods (antenatal, birth, and postnatal). Methods: A survey was sent to 2, 048 women who gave birth at seven public hospitals in New South Wales, Australia, exploring their expectations of, and experiences with maternity care. Women's overall ratings of care for the antenatal, birth, and postnatal periods were analyzed, and a number of maternal characteristics and care factors examined as potential predictors of "Very good" ratings of care. Results: Among 886 women with a completed survey, 65 percent assigned a "Very good" rating for antenatal care, 74 percent for birth care, 58 percent for postnatal care, and 44 percent for all three periods. One factor was strongly associated with care ratings in all three maternity periods: women who were "always or almost always" treated with kindness and understanding were 1.8–2.8 times more likely to rate their antenatal, birth, and postnatal care as "Very good." A limited number of other factors were significantly associated with high care ratings for one or two of the maternity periods. Conclusions: Women's perceptions about the quality of their interpersonal interactions with health caregivers have a significant bearing on women's views about their maternity care journey.